Examining the effects of upward social mobility on women’s workplace experiences in China - Ding, Wei; Wang, Wen-Cheng (Frontiers in Psychology, 2025)
This study examines how upward social mobility shapes Chinese women’s workplace experiences by applying social comparison theory and asking which structural-related factors most strongly influence women’s perceptions of—and strategies for—occupational advancement in contemporary China. Employing Latent Dirichlet Allocation (LDA) topic modeling on 4,043 Zhihu comments under the “involution” discussion, we identify five operational dimensions—economic reward–value alignment, work burden, institutional environment, resource distribution, and individual agency—that collectively explain variation in perceived mobility opportunities. Our results show that misalignment between compensation and perceived professional worth, coupled with excessive instructional and emotional labor, constitutes a primary barrier, whereas supportive institutional policies and strong professional identity mitigate constraints. These findings offer actionable insights for policymakers and educational leaders to reform compensation structures and workload management, thereby fostering more equitable career advancement for women in China.